2019
DOI: 10.1002/ird.2337
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Irrigation Scheduling Systems in Germany: Survey of the Users and Comparative Study

Abstract: In Germany, the irrigation sector accounts for only 1% of water use. In recent years, however, this sector has attracted more attention due to the occurrence of severe drought periods. Irrigation scheduling systems could support adaptation strategies but little is known about current providers, performance and users. In this study we aimed to depict the current situation of the existence and functioning of irrigation scheduling systems available in Germany. Six methods were identified and assessed based on dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Most complex strategies to increase water and energy savings in irrigation, including implementation of irrigation decision support systems, which integrate soil water parameters, local climate data, plant water requirement, and soil water monitoring tools to enhance decision making when applying individual regulatory and technical approaches, face significant challenges on ground. Apart from the more technical factors that were recently reported by the international community (Baroni et al ., 2019; Srinivasan et al ., 2019), attention should be directed to improved consideration of farmers’ needs and expectations (Alexander et al ., 2020; Pagliacci et al ., 2020) to avoid policy failure originating from insensitivity to various socio‐economic and cultural factors influencing adoption of innovations (Röling, 2009; Howley, Donoghue, & Heanue, 2012; Dogliotti et al ., 2014; Srinivasan et al ., 2019). The implementation of technically most complex tools, such as irrigation decision support systems, needs to be viewed together with improved on‐farm support and constant work with the farmers.…”
Section: Discussionmentioning
confidence: 99%
“…Most complex strategies to increase water and energy savings in irrigation, including implementation of irrigation decision support systems, which integrate soil water parameters, local climate data, plant water requirement, and soil water monitoring tools to enhance decision making when applying individual regulatory and technical approaches, face significant challenges on ground. Apart from the more technical factors that were recently reported by the international community (Baroni et al ., 2019; Srinivasan et al ., 2019), attention should be directed to improved consideration of farmers’ needs and expectations (Alexander et al ., 2020; Pagliacci et al ., 2020) to avoid policy failure originating from insensitivity to various socio‐economic and cultural factors influencing adoption of innovations (Röling, 2009; Howley, Donoghue, & Heanue, 2012; Dogliotti et al ., 2014; Srinivasan et al ., 2019). The implementation of technically most complex tools, such as irrigation decision support systems, needs to be viewed together with improved on‐farm support and constant work with the farmers.…”
Section: Discussionmentioning
confidence: 99%
“…Despite difficulties being identified in relation to the integration of an IAS in some contexts (such as the technical limitations or performance of the IAS), these services were shown to be a relevant support for the improvement and assessment of the agricultural water management [20]. The authors of [21] showed that, in the irrigated district of Baixo Acaraú in Brazil, the implemented IAS improved water irrigation management in most areas when farmers followed the advised crop irrigation requirements.…”
Section: Introductionmentioning
confidence: 99%
“…A lack of consistency between environmental variability and irrigation system design, insufficient information on plant water demand and spatial variability within farms and low control of the water distribution network limits IDSSs' contribution to efficient water use and agricultural climate-change resilience [14]. The use of IDSSs by farmers is far below what is possible [15,16]. Some researchers [16] consider linear, technology-supported approaches to be the main reason for this.…”
Section: Introductionmentioning
confidence: 99%